Hypertension After Kidney Donation: Incidence, Predictors and Correlates - Sanchez, Otto A. (Am J Transplant, 2018)
Incidence of post-donation hypertension, risk factors associated with its development and impact of type of treatment received on renal outcomes were determined in 3700 kidney donors. Using Cox proportional hazard model, adjusted hazard ratios (HRs) for cardiovascular disease (CVD), estimated glomerular filtration rate (eGFR) <60, <45, <30 mL/min/1.73m(2), end stage renal disease (ESRD) and death in hypertensive donors were determined. After a mean (SD) of 16.6 (11.9) years of follow-up, 1126 (26.8%) donors developed hypertension and 894 were receiving anti-hypertensive medications. Hypertension developed in 4%, 10% and 51% at 5, 10, and 40 years, respectively and was associated with proteinuria, eGFR < 30, 45 and 60 mL/min/1.73m(2), CVD and death. Blood pressure was <140/90 mmHg at last follow-up in 75% of hypertensive donors. Use of angiotensin-converting enzyme inhibitors or angiotensin receptor blockers (compared to other antihypertensive agents) was associated with lower risk for eGFR <45 mL/min/1.73m(2), HR 0.64 (95% CI 0.45–0.9), p = 0.01 and also less ESRD; HR 0.03 (95% CI 0.001–0.20), p = 0.004. In this predominantly Caucasian cohort, hypertension is common after donation, well controlled in the majority of donors and factors associated with its development are similar to those in the general population.